Sourcing strategies, channels and geographies in the international recruitment of a highly skilled work-force - Bruland, Silja K.; Rusten, Grete (ERDKUNDE, 2012)
The geographical dimension covered by the international migration research literature is usually concerned with a host-/home-country perspective. However, little attention has been paid to the function of the region as a “clearing house” through which companies in a recruitment process can identify and screen potential candidates that have already settled the country. This paper investigates the recruitment channels used by companies for recruiting highly skilled internationals to the Sunnhordland region in Norway. The empirical evidence, combining secondary data and company case study data, has shown that regional and national recruitment channels play important roles in the search for highly skilled migrants that originally come from outside Norway. In particular, the data show two important roles of higher education in Norway. The first is in the training of suitable candidates originally from outside Norway in accordance with the needs of Norwegian businesses. The second is the way in which years spent in Norway as a student represent an important “testing ground” for individuals considering future settlement in the country. The ability to find information about potential candidates directly through references, on the basis of who the candidates have worked for, or inquiring through more informal networks, further demonstrate the value of the region’s role in recruitment, starting from the sourcing process to choice and attractiveness of the destination in question.